Net primary production of Laminaria hyperborea along the vertical depth profile based on different diffuse attenuation coefficients - Franke, Kiara; Matthes, Lisa C; Graiff, Angelika; Karsten, Ulf; Bartsch, Inka (In: Franke, K et al. (2023): Dataset for estimating the photosynthetic oxygen production of Laminaria hyperborea off the island of Helgoland in summer 2014 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.958950, 2023)
Over the whole water column, daily diffuse attenuation coefficient (Kd in 1/m) values are based on in situ photosynthetically active radiation (PAR) measurements performed in different depths (1.2, 2.9, 4.4, 6.6 m) during summer 2014. PAR for the algae collection depths is calculated based on daily Kd values. Daily net primary production (NPP in g C/m² seafloor/day) for each sampling depth is calculated with in situ vertical profiles based on daily Kd, leaf area index (Pehlke and Bartsch, 2008) and a photosynthetic quotient (PQ) of 1.18 (Miller III et al. 2009). For comparative purposes, daily NPP values were also calculated using the measured maximum and minimum daily Kd and the mean Kd, which were derived from all daily Kd over the entire sampling period.
Keywords: blade gradient; Chlorophyll a; depth gradient; diffuse attenuation coefficient; dry mass/area ratio; Fv/Fm; Helgoland; in situ PAR; Kelp; net primary production; oxygen evolution; photoacclimation; Photosynthesis versus irradiance curves; Primary production